2017
DOI: 10.1016/j.jsps.2017.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic detergents: 100 years of history

Abstract: In the year 2016 the synthetic detergents complete 100 years and in this story they evolved as cleaners. They are already part of the routine of thousands of people worldwide. For a higher power of cleaning of the detergent, today, are added phosphates, the main responsible for environmental problems. After 100 years of synthetic detergents, the effect of the combination of various cleaners on the environment is a gap. Legislation and guidelines about the other components of the formula of cleaners still missi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 12 publications
0
42
0
3
Order By: Relevance
“…Although the field of synthetic detergent chemistry is well established, with first reports more than 100 years ago 8 , suitable detergents for membrane protein research are still typically identified by trial and error. The number of detergent families is staggeringly diverse and their chemical variety makes it increasingly difficult to define design guidelines to predict the utility of detergents for purifying membrane proteins.…”
mentioning
confidence: 99%
“…Although the field of synthetic detergent chemistry is well established, with first reports more than 100 years ago 8 , suitable detergents for membrane protein research are still typically identified by trial and error. The number of detergent families is staggeringly diverse and their chemical variety makes it increasingly difficult to define design guidelines to predict the utility of detergents for purifying membrane proteins.…”
mentioning
confidence: 99%
“…Keunggulan zeolit dibandingkan dengan STPP sebagai builder adalah terdapat pada komposisinya. STPP yang mengandung fosfat dapat menyebabkan eutrofikasi, sedangkan pada zeolit mengandung silikat dan aluminat yang tidak mencemari lingkungan [16].…”
Section: Pembuatan Deterjen Cairunclassified
“…The process of soap making could apply to the production of soaps from waste frying oils, giving it attributes of the technology with a green perspective [14]. Although natural soaps were considered environmentally friendly, there are still some adverse effects on the ecosystem, which can be observed (such as forming the insoluble films on water surfaces that decrease entry of the oxygen to the water) [15]. The soap as a constituent of the wastewater can be successfully treated by chemical (coagulation) and biologic means (using microorganisms) [16].…”
Section: Introductionmentioning
confidence: 99%